Mutations in the maternally imprinted gene MKRN3 are common in familial central precocious puberty. Issue 1 (January 2016) - Simon, Dominique; Ba, Ibrahima; Mekhail, Nancy; Ecosse, Emmanuel; Paulsen, Anne; Zenaty, Delphine; Houang, Muriel; Jesuran Perelroizen, Monique; de Filippo, Gian-Paolo; Salerno, Mariacarolina; Simonin, Gilbert; Reynaud, Rachel; et al.
Abstract : Context and objective: Idiopathic central precocious puberty (iCPP) is defined as early activation of the hypothalamic–pituitary–gonadal axis in the absence of identifiable central lesions. Mutations of the makorin RING finger 3 ( MKRN3 ) gene are associated with iCPP. We aimed to assess the frequency of MKRN3 mutations in iCPP and to compare the phenotypes of patients with and without MKRN3 mutations. Design: An observational study was carried out on patients recruited at pediatric hospitals in France and Italy. Forty-six index CPP cases were screened for mutations in the MKRN3 coding sequence: 28 index cases of familial cases and 18 cases did not report any familial history of CPP. The endocrine phenotype was compared between MKRN3 mutated and non-mutated patients. Results: MKRN3 mutations were identified in one sporadic and 13 familial cases. We identified five new heterozygous missense mutations predicted to be deleterious for protein function and two frameshift mutations, one new and the other recurrent, predicted to result in truncated proteins. Age at puberty onset varied very little among patients with MKRN3 mutations and puberty occurred earlier in these patients than in those without MKRN3 mutations (6.0 years (5.4–6.0) vs 7.0 years (6.0–7.0), P =0.01). Conclusions: MKRN3 mutations are common in familial iCPP. MKRN3 is one of the gatekeepers of the postnatal activation of the gonadotropic axis.